INDUKSI KETAHANAN KEKERINGAN DELAPA N HIBRIDA KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN SILIKA - , AMANDA YASHINTA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objectives of this re search were 1) to study the response of eight hybrids of oil palm to the silica (Si) application under drought stress, 2) to de termine the optim al dose of Si that able to induce the resistance of eight oil palm hybrids to drought stress. The research was conducted at Bend osari, Madure jo, Prambanan, Slema n, Yogyakarta from May 2013 to February 2014. The fie ld expe rime nt w as arrange d in Random ized Complete Block De sign (RCBD) factorial, with three blocks as replications. The first factors were the hybrid s of oil palm, name ly Y angam bi, A VRO S, Langkat, PPKS 239, Simalungun, PPKS 718, PPKS 540 and D umpy. The second factor s were the Si application s, namely 0.00